Combustion of lignite carbon under agitation - Duranay, ND; Pehlivan, D (Elsevier Science Bv, 2005)
To get insights into the burning of large coal particles as agitated beds in the recently developed rotary chambers, combustion behaviour of eight Turkish lignites was studied in a laboratory-size rotating wire mesh basket. Single particles from 0.5 to 5 g average weight were loaded in the basket, which was then inserted into a preheated tube furnace. The net effect of removing ash continuously as a result of agitation on the combustion rates and times was searched for all the lignites, whereas the other parameters, such as rotation speed of the basket, particle size, temperature and air velocity, were investigated on only 1 an lignite. Because both volatile and char combustion times and their confident prediction have important bearings in the design and capacity of coal combustion systems, experimentally determined char combustion rates and times were compared to those found by using double resistance theory. It was observed that combustion of lignite chars in the agitated beds proceed faster and lasted in shorter times as expected, mainly due to the removal of ash layer by agitation during the period of char combustion. The influence of the agitation on the combustion of chars from lignites with high-volatile matter content was especially noticeable. Combustion rates increased more as the speed of basket was increased. A combined control mechanism could be used to describe combustion rates of lignite chars. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: lignite; combustion; agitation